2021
DOI: 10.1186/s12885-021-09006-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel metabolism-related gene signature associated with the survival of bladder cancer

Abstract: Background Bladder cancer (BC) is one of the most common malignancies and has a relatively poor outcome worldwide. In this study, we attempted to construct a novel metabolism-related gene (MRG) signature for predicting the survival probability of BC patients. Methods First, differentially expressed MRGs between BC and normal samples were identified and used to construct a protein-protein interaction (PPI) network and perform mutation analysis. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Li X et al. identified LRP1 as a metabolism-related gene that is associated with the survival of BLCA ( 29 ), and Xing P et al. revealed that LRP1 was involved in regulating the immune infiltration level in BLCA ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li X et al. identified LRP1 as a metabolism-related gene that is associated with the survival of BLCA ( 29 ), and Xing P et al. revealed that LRP1 was involved in regulating the immune infiltration level in BLCA ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing research has shown that lipid metabolic dysregulation is directly related to the emergence of inflammation, cancer, and medication resistance [ 23 ]. Recent research indicates that all metabolic pathways, including those for glucose, amino acids, nucleotides, and other pathways, may function as possible prognostic biomarkers for BLCA [ 24 ], on their molecular-level metabolic control, few investigations have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…LRP1, a member of the low density lipoprotein receptor family of proteins encoded by this gene, is involved in a variety of cellular processes, including intracellular signal transduction, lipid homeostasis and the elimination of apoptotic cells [23] . It was included in one of the prognostic evaluation genes of BLCA by many authors [24,25] .…”
Section: Discussionmentioning
confidence: 99%